Investigating the antioxidant effects of Cucurbita maxima Duchesne extract on motor coordination and memory impairment induced by scopolamine in rats - Najmeh Asgharzadeh; Fatemeh Azizi; Mohammadreza Hojjati; Leila Roohi; Zahra Rabiei; Mehrdad Shahrani-Korani (Future Natural Products)
Background and aims: Cucurbita maxima Duchesne is a member of the Cucurbita genus within the Cucurbitaceae family. The consumption of C. maxima (CM) offers several health benefits due to its antioxidant, anti-inflammatory, and antidiabetic properties, as well as its rich content of bioactive compounds. The primary aim of this study is to investigate the effects of CM extract on motor coordination and memory deficits induced by scopolamine (SCOP). Methods: In this experimental study, 56 Wistar rats were divided into eight groups. To induce memory impairment, SCOP was administered at a dose of 1 mg/kg body weight via intraperitoneal injection (i.p.) daily for 21 consecutive days. A hydroalcoholic extract of CM was prepared using 70% ethanol and administered at concentrations of 50, 100, and 200 mg/kg (i.p.) for the same duration. The effects were evaluated using the shuttle box, Morris water maze (MWM), and rotarod tests. Additionally, serum and brain levels of malondialdehyde (MDA) and total antioxidant capacity (TAC) were measured. Results: The results from the MWM indicated that animals receiving SCOP along with CM extract at concentrations of 50, 100, and 200 mg/kg spent significantly more time on the target platform compared to the SCOP-only group. In the shuttle box test, the secondary latency time of rats treated with SCOP and CM extract at the same concentrations was significantly longer than that of the SCOP group. Additionally, no significant effects were observed on motor coordination. The CM extract at concentrations of 50 and 200 mg/kg significantly reduced brain levels of MDA and increased TAC compared to the SCOP group. Conclusion: Cucurbita maxima extract effectively improves memory deficits induced by SCOP by reducing oxidative stress.